The Role of International Office at Open University: A Comparative Analysis of Best Practices and Organizational Learning Strategies - Phukkeson, Rattip (LPPM Universitas Terbuka, 2025)
This study investigates the role of international office in promoting institutional excellence at open universities. Through a qualitative case study and comparative analysis of twelve open universities in China, Hong Kong, Indonesia, Japan, Korea, Malaysia, the Philippines, Sri Lanka, Turkey, and Vietnam, the research identifies areas for improvement and explores strategies to foster organizational learning. Key findings include the need for enhanced initiatives, addressing challenges, strengthening internal collaboration, and measuring the impact of internationalization efforts. Recommendations focus on implementing best practices, fostering a culture of continuous learning, and integrating learning outcomes into international affairs initiatives. This study provides actionable insights for open universities to advance their internationalization agendas and achieve excellence.